A case study to increase sales of Padu*Mobile: the product of HeiTech Padu Berhad / Nor Atiqah Abdul Razak - Abdul Razak, Nor Atiqah (Faculty of Business and Management, 2010)
The relationship between marketing strategy and performance has been well documented. Successful marketing strategy basically depends on the firm’s ability to identify and influence the flows of customers into and out of the market. Marketing strategy requires these three decisions; where to compete, how to compete and when to compete (Chapter 2, Strategic Marketing). Good marketing strategy is become very important to HeiTech Padu Berhad since its product, Padu*Mobile, fail in the market. HeiTech Padu Berhad was launched Padu*Mobile on August 13th 2008, and the launching ceremony held at Impiana Hotel on November 25, 2008. Marketing strategies are generally concerned with 4P’s; product strategies, pricing strategies, promotional strategies, and placement strategies. But in this case study, the focus only on the promotional strategies since one of the factors contribute to the Padu*Mobile failure is the lack of promotional activities. The company needs to effectively utilize its entire promotional staff in a manner that a strength of one is use to offset the weakness of other to achieve its organizational goals and objectives, this can be done through appropriate promotional strategy or plan. The main objective of promotion is to build awareness, create interest, provide information, boost demand, and create brand awareness, brand loyalty and preferences.